The method of manure decontaminating and obtaining high-quality fertilizer from it - Korchan , L. M.; Pysarenko , P. V.; Korchan , M. I. (Scientific Progress & Innovations, 2019)
The purpose of the article is to create a cheaper and more effective method of decontaminating animal manure, to reduce the time of manure treatment, and to improve the quality of fertilizers obtained from it. Research methods. In our experimental research the stacks of cattle and goat solid litter manure were set and then treated in layers with various ratios of iodine-bromine mineralized reservoir water (hereinafter referred as the MRW) of the Reshetniaky deposit. Control stacks of manure were not treated by MRW. Every 15 days after stacking, manure samples were taken to study the process of manure decontamination from bacterial and invasive pathogens. The research results. The results of the conducted microbiological and helminthological studies showed complete decontamination of manure from pathogenic micro-flora, eggs and larvae of helminthes on the 30-45th day in the summer and 60-90th day in the winter period of the year in experimental manure stacks after its layered treatment by MRW in volumetric ratios of 50 liters/m3 of manure. In control stacks, manure remained not decontaminated throughout the observation period. It was also proved that after treating manure with MRW there is a significant increase of organic matter and nutrient elements in it: total nitrogen, nitrogen of ammonium phosphorus and potassium. The elements of scientific novelty. The offered method of decontaminating manure and obtaining high quality fertilizer from involves the addition of an active component to accelerate the process of animal manure bio-thermal decontamination by layer treating it with natural mineral – iodine-bromine mineralized reservoir water. Practical significance. The offered method of decontaminating manure receiving a high quality fertilizer from it is cheap, efficient, and enables to accelerate the process of bio-thermic decontamination of animal manure, significantly reduce environmental pollution and it can be used as a means of increasing the nutrient effectiveness of organic fertilizers. The fact that the reserves of this natural mineral in Ukraine are unlimited significantly increases the practical interest in MRW.